Parallel computer in production. - Cui Lili (Beijing Review, 1994)
After more than a year of effort, China's State Intelligent Computer Research and Development Center has manufactured the country's first CICS-01 parallel computer. This top-level computer system is equivalent to counterparts produced outside China in 1992. The CICS-01 has been evaluated by the state, and it is believed that the system can act not only as a focal device suitable for major business and data processing, but as a central mainframe for higher learning and research institutions. The system provides powerful software capabilities and is an ideal general purpose platform for scientific and engineering calculations, artificial intelligence, and real-time computing.